PTSD symptom cluster severity predicts momentary emotion dynamics during couple conversations - Fredman, Steffany J.; Fischer, Melanie; Baucom, Donald H.; Le, Yunying; Taverna, Emily C.; Chow, Sy-Miin; Ram, Nilam; Marshall, Amy D. (Behavior therapy, 2023)
This study investigated the associations between momentary emotion dynamics and posttraumatic stress disorder (PTSD) symptoms. Using a sample of 61 couples (N=122 individuals) in which all individuals were trauma exposed and at least one partner screened positive for PTSD, we examined the intra- and interpersonal regulation of vocally encoded emotional arousal (fundamental frequency [f0]) and how these momentary emotion regulatory patterns relate to specific PTSD symptoms during two couple conversations: one designed to elicit conflict and one to elicit intimacy. PTSD symptoms were assessed using a gold standard clinical interview. In both conversations, higher reexperiencing symptoms were associated with greater emotional inertia (i.e., more resistance to change in emotional state following deviation from one’s emotional equilibrium), and higher avoidance symptoms were associated with less emotional inertia (i.e., quicker return to emotional equilibrium). In the intimacy conversations, individuals also responded to their partners’ arousal. Furthermore, individuals whose partners exhibited higher emotional numbing symptoms exhibited more emotional inertia, suggesting that emotion regulation may be a function of both one’s own and one’s partner’s PTSD symptoms. Attending to the interpersonal context of emotion dynamics during PTSD treatment may enhance outcomes.